PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN WALI MURID PADA LEMBAGA PAUD AR-RIDHO, DI KEC. CIBUNGBULANG, BOGOR - Lia Maryani; Subanul Yaum; Sidiq, Fajar (Indonesian Journal Entrepreneurship Finance and Business Management, 2024)
This study aims to produce information in the form of a more in-depthexplanation of the influence of service quality and price on customersatisfaction. And obtain results from processed data about how muchinfluence service quality and price have on customer satisfaction.The method used in this study is descriptive and verificationwith a population and sample of 32 parent’s respondents, processingdata using the SPSS Version 25 application.Journal homepage: http://ijefbm.stiembi.ac.id/index.php/ijefbmIndonesia Journal Economic, Finance, Business and Management  102The results of the regression equation are Y = 9.572 + 0.299X1+ 0.472X2 + e, using the multiple regression analysis method. Theresults of the Hypothesis Testing, obtained that the service variable hasa value of sig < 0.05, which is 0.010, which means it is significant. Theresult of T-count = 2,738 > T-table = 1,697. Then the service variable ispositively and significantly related tocustomer satisfaction and theservice variable has a value of sig < 0.05, which is 0.000 which meanssignificant. The result of T-count = 4,525 > T-table = 1.697. Then the pricevariable is positively and significantly related tocustomer satisfaction.Simultaneously, the variables of service and price can have a positiveeffect on customer satisfaction with a calculated F-value of 30,854 > Ftable of 3.29 with a significant level of 0.00 < 0.05. So the results ofhypothesis testing are: H1, H2, H3 accepted and H0 rejected. Theresults of the correlation coefficient obtained that the r value of service=0,674 and the r value of the price = 0,773 this means that there is a strongand positive relationship which indicates that increasing serviceandthe price in general can improve customer satisfaction. The result of KD(R^2) = 0,658. This means that 65,8% of the independent variables,namely serviceand price, can be explained by the dependent variable,namelycustomer satisfaction. The remaining 34,2% is explained byother factors not examined by this study.